2022
DOI: 10.12998/wjcc.v10.i30.11111
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous bilateral femur neck fracture secondary to grand mal seizure: A case report

Abstract: BACKGROUND Spontaneous bilateral femur neck fracture is a rare entity in the general population. CASE SUMMARY A 17-year-old immobile, developmentally delayed male with the sequelae of cerebral palsy fractured both femoral necks during a grand mal epileptic seizure. He had been treated with valproic acid as an antiseizure medication for about 10 years; otherwise, he had no history of drug use. The laboratory analysis was normal except a marked vitamin D deficiency. Close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Simultaneous bilateral femur neck fracture in the absence of significant trauma is extremely rare in children. Unlike the elderly population where osteoporosis is a common cause, children usually have an underlying metabolic bone disease rendering them vulnerable to break with trivial trauma ( Table 2 ) [ 3 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 ]. Steinwender et al reported a case of benign osteopetrosis in a 7-year-old boy who was asymptomatic till a bilateral femoral neck fracture occurred [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous bilateral femur neck fracture in the absence of significant trauma is extremely rare in children. Unlike the elderly population where osteoporosis is a common cause, children usually have an underlying metabolic bone disease rendering them vulnerable to break with trivial trauma ( Table 2 ) [ 3 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 ]. Steinwender et al reported a case of benign osteopetrosis in a 7-year-old boy who was asymptomatic till a bilateral femoral neck fracture occurred [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steinwender et al reported a case of benign osteopetrosis in a 7-year-old boy who was asymptomatic till a bilateral femoral neck fracture occurred [ 3 ]. An association has also been reported with seizure disorders secondary to hypocalcemia, autism, cerebral palsy, and electroconvulsive therapy [ 8 , 9 , 10 , 12 ]. The muscle contractions during an epileptic episode can produce excessive rotational stress, thereby producing bilateral neck femur fractures.…”
Section: Discussionmentioning
confidence: 99%